Analisis Pengaruh Ketersediaan Fasilitas Kerja dan Tingkat Disiplin Kerja terhadap Kinerja Para Perangkat Desa pada Kecamatan Babat Toman Kabupaten Musi Banyuasin - Anggraini, Bertha; Nenny Octarinie (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2022)
The purpose of the study is to analyze the influence on the availability of work facilities and work discipline of village officials in Babat Toman District, Musi Banyuasin Regency. Quantitative research is used by conducting observations and also distributing questionnaires to 30 respondents. The results of the analysis show that the provision of work facilities and the application of work discipline to village officials at the Babat Toman sub-district office, Musi Banyuasin Regency are generally good. This can be shown from the high response of respondents to the conditions of each research variable. There is an influence between office facilities and work discipline on the performance of village officials in Babat Toman District, Musi Banyuasin Regency. The magnitude of the effect simultaneously is 76.5% and the remaining 23.5% is influenced by other factors outside of this study.